Contemporary Concepts in the Volleyball Training - Ivanov, Petar (Research Papers, 2021)
The purpose of the current study is to explore and analyze some of the contemporary concepts in developing the volleyball training. Various approaches are presented in structuring the workout. Considerations have been given on the physical exercises and recovery. The benefits of using a certain type of training are emphasized, as well as their place and role in the training of highly qualified volleyball players throughout the year. Special attention is paid to ball control exercises as a tool of complex development of high-speed qualities and high-speed technical and tactical skills. The individual training of the volleyball player as a modern form of work, which reflects the creative demand of coaches and athletes for effective training and improvement, is also addressed. The studied and analyzed concepts in the contemporary volleyball training would be useful for volleyball professionals in the course of their professional work.